(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
How teachers read or interpret textbooks, which represent curricula, is important for successful implementation of curricula (the level of reading of knowledge, skills and values in the textbooks that curriculum sets forth for students’ learning). This paper aims to investigate how middle school mathematics teachers read mathematics textbooks in the light of goals of middle school mathematics curriculum. To this end, a 5th grade mathematics textbook’s segment which covers one learning objective about simplifying and expanding fractions is given to 30 middle school mathematics teachers and they are asked this following question: “What do think that the textbooks writers pay attention for teaching of this learning objective?” The findings reveal that the teachers did not read such mathematical process skills as reasoning, making connection, and communication which were reflected into the learning objective in the textbook. The findings also show that the teachers mainly read the textbooks by “describing what is done”, “providing suggestion”, and “pointing out short comings” and these suggest that this type of reading is rather superficial as far as the teaching that the curriculum aims to achieve is concerned. The paper draws attention to the issues regarding how the textbook reading skills of mathematics teachers can be developed and presents some implications about textbook research.